Speech performance and training effects in the cochlear implant elderly - Schumann, Annette; Hast, Anne; Hoppe, Ulrich (Audiology and Neuro-Otology, 2014)
Cochlear implantation requires acclimatization to the electrical input. Usually, cochlear implant (CI) listeners undergo an auditory rehabilitation program that includes auditory training sessions. Recently, it was shown that a phoneme-based training may improve speech perception abilities even in experienced CI listeners. The current study focuses on whether the effect of an auditory training program depends on the age of CI listeners.Fifteen CI listeners took part in an auditory phoneme-based computer training program. Before and after training, speech recognition tests in moderate and difficult noise (+5 dB SNR and 0 dB SNR, respectively) were administered. Additionally, speech recognition was tested 6 months after the training (follow-up). A control group consisting of 12 subjects underwent audiometric testing without any auditory training.Speech perception in moderate noise improved significantly during the training as revealed by comparing pre- and posttraining scores evaluated in the moderate noise condition. No significant change was observed for the difficult noise situation at 0 dB SNR. The speech perception measures of the control group remained unchanged. No significant effect of age on the training effect was observed.Speech recognition can be improved even in experienced CI listeners. When motivated to participate, senior CI users with long-term CI experience may benefit in a similar way from an auditory, phoneme-based computer training program as younger CI users.
EVALuna2:19974